Cytological Features of a Variant NUT Midline Carcinoma of the Lung Harboring the NSD3-NUT Fusion Gene: A Case Report and Literature Review. (19th January 2015) - Kuroda, Shiho; Suzuki, Shioto; Kurita, Akira; Muraki, Mari; Aoshima, Yoichiro; Tanioka, Fumihiko; Sugimura, Haruhiko
Abstract : Background . Nuclear protein in testis (NUT) midline carcinoma (NMC) is a very rare and aggressive malignancy. In more than two-thirds of these NMC cases, a fusion between NUT and BRD4 or BRD3 has been documented; other variants are rare. The cytology of NMC itself has been sparsely documented and that of variant NMC has never been reported. Case Presentation . A 36-year-old woman was admitted because of a rapidly progressing lung tumor with metastases to the breast and bone. We recently reported this patient as the first case of a variant NMC of the lung harboring an NSD3-NUT fusion, based on immunohistochemical and genetic analyses. Cytological material was available for the present review. A highly cellular smear contained a predominantly noncohesive pattern of monomorphic cells with diameters 2–2.5 times greater than those of small lymphocytes, with a round-to-oval nucleus, slightly irregular nuclear contours, variably prominent nucleoli, scant cytoplasm, and identifiable mitotic figures. Foci of stratification and overt pearl formation, including a dyskeratocyte, were occasionally observed. The necrotic background contained naked nuclei, karyorrhectic debris, apoptotic cells, and macrophages phagocytizing karyorrhectic debris; nuclear crushing was noted. Conclusion . The cytological features of a variant NMC of the lung are described for the first time.